2004
DOI: 10.1136/thx.2003.011759
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of tuberculosis from smear negative patients: a molecular epidemiology study

Abstract: Background: While smear positive patients with tuberculosis (TB) are considered more infectious than smear negative patients, the latter can also transmit TB. Methods: In a molecular epidemiology study of 791 patients in the Greater Vancouver regional district, the number of episodes of TB transmission from two groups of smear negative clustered patients by RFLP (assumed to be involved in recent transmission) was estimated after assessing for potential bias. Group 1 (n = 79) included patients with pulmonary TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
131
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 17 publications
9
131
0
7
Order By: Relevance
“…We based our calculations on two molecular studies: First a study in Greater Vancouver, Canada, which determined that ss-cases are responsible for at least one-sixth of culture-positive episodes of TB transmission [35]. Secondly, a study in San Francisco, California, found that the source patient was ss-in at least 17% of the registered episodes of transmission, and it was estimated that ss-patients were 22% as likely as ss+ patients to transmit TB [36].…”
Section: The Contribution Of the Sputum Smear-negative Casesmentioning
confidence: 99%
“…We based our calculations on two molecular studies: First a study in Greater Vancouver, Canada, which determined that ss-cases are responsible for at least one-sixth of culture-positive episodes of TB transmission [35]. Secondly, a study in San Francisco, California, found that the source patient was ss-in at least 17% of the registered episodes of transmission, and it was estimated that ss-patients were 22% as likely as ss+ patients to transmit TB [36].…”
Section: The Contribution Of the Sputum Smear-negative Casesmentioning
confidence: 99%
“…This may result in delays in diagnosis, 6 which in turn can be associated with progression of disease, worse treatment outcome and spread of TB in the community. [7][8][9] To our knowledge, there is little local or published evidence about the practice of or time taken for diagnosing smear-negative PTB in the Pacifi c Islands, although TB surveillance data are reported annually. 1,2 These data report the proportion of all TB cases diagnosed as PTB (both smear-positive and smear-negative) and extra-pulmonary TB, but do not report the number of smears for each case, how this relates to the age and sex of the patients or the time taken for diagnosis.…”
mentioning
confidence: 99%
“…2 A molecular epidemiological study was conducted in two groups (Group 1, PTB or PTB + EPTB; Group 2, Group 1 + EPTB) in Vancouver General Hospital to trace the transmission chain of smear negative tuberculosis. 1 It revealed that the proportion of episodes of transmission was 17% to 21% in Group 1 and 25% to 41% in Group 2. The result showed that the smear negative TB transmission accounted for at least one sixth of the total culture positive TB cases.…”
mentioning
confidence: 99%
“…In contrast, patients whose bacillary load is less than the mentioned number are not detected by the smear microscopy. 1 Smear positive patients spreads the infections to others and TB control programmes are aggressive in early diagnosis of smear positive TB patients. It has been believed that smear positive patients spreads the disease and smear negative cases are less infectious than the smear positive cases and do not contribute for transmission.…”
mentioning
confidence: 99%